Multimedia Development of Integer Concept Material for Slow Learning Students Learner - Zefanya Dwicahya; Erlina Prihatnani; Fika Widya Pratama (FKIP - Universitas Riau, 2026)
This research is motivated by the difficulties of slow learner students in understanding the basic concepts of integers, such as recognizing the meaning of negative numbers, comparing numbers, and representing numbers on a number line, which has an impact on the low understanding of mathematical concepts on an ongoing basis. This research aims to develop valid, practical, and effective learning multimedia to help slow learner students understand the concept of integers in a more structured and in-depth manner. The method used was Research and Development (R&D) with the ADDIE model, which includes analysis, design, development, implementation, and evaluation. The research subjects consisted of nine slow-learning students at a public junior high school in Salatiga who had been identified through psychological testing. This research was conducted from February to March 2026. Data collection techniques include interviews, tests (pre-test and post-test), and validation and practicality questionnaires, while data analysis is carried out descriptively quantitatively and inferentially using statistical tests. The results of the study indicate that the multimedia